2017
DOI: 10.3126/jkmc.v5i2.18408
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of serum lactate level in septic shock at Emergency Department of Patan Hospital, Nepal

Abstract: Background: Sepsis is a leading cause of death in emergency department. Serum lactate level assessment can play an important role for risk assessment and prognostication in critically ill septic patient. Objective: The objective of this study is to determine the relevance of initial serum lactate measurement after the implementation of sepsis protocol in emergency department, based on guidelines of Surviving Sepsis Campaign. Methods: This was a cross sectional descriptive study conducted at Patan Hospital from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…A similar study was done in Patan Hospital in a total of 94 patients which showed abnormal Lactate levels in 80% among which 29% had intermediate lactate levels and half of them had high lactate levels which were unlike our findings which showed that 28.3% had intermediate and 18.9% had high lactate level. 6 On comparing the normal and abnormal lactate levels according to gender, the above study showed that among total females, 13.1% have normal lactate levels and 86.9% have abnormal while in males, 7.1% have normal lactate levels and 92.9% have abnormal, 6 unlike our study which showed that 56.5% of females have normal lactate level with 43.5 having abnormal and for males, the percentage is equally divided into halves.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…A similar study was done in Patan Hospital in a total of 94 patients which showed abnormal Lactate levels in 80% among which 29% had intermediate lactate levels and half of them had high lactate levels which were unlike our findings which showed that 28.3% had intermediate and 18.9% had high lactate level. 6 On comparing the normal and abnormal lactate levels according to gender, the above study showed that among total females, 13.1% have normal lactate levels and 86.9% have abnormal while in males, 7.1% have normal lactate levels and 92.9% have abnormal, 6 unlike our study which showed that 56.5% of females have normal lactate level with 43.5 having abnormal and for males, the percentage is equally divided into halves.…”
Section: Discussioncontrasting
confidence: 73%
“…A study revealed a result similar to our study which showed that the maximum number of patients (49.9 %) had low lactate levels, with ours being 52.8%. 6 However, contrary to this, another study shared that the maximum patient has intermediate lactate levels (45.3%). 7 Shock index (SI), is a simple and effective bedside assessment means of gauging the degree of shock and is as defined as heart rate divided by systolic blood pressure (SBP) with a normal range of 0.5 to 0.7 in healthy adults.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation